Here lies Lalo : the collected poems of Abelardo Delgado - Abelardo, 1931-2004 (Arte Publico Press, 2011)
Delgado used his words to fight for justice and equal opportunity for people of Mexican descent living in the United States. A twelve-year-old when he emigrated from northern Mexico to El Paso, Texas, Delgado's development as a poet and writer coincided with the Chicano Civil Rights movement, and so his poems both reflect the suffering of the oppressed and are a call to action. Available for the first time to mainstream audiences, Delgado's poems included in this landmark volume were written between 1969 and 2001, and are in Spanish, English, and a combination of both languages. While many of his poems protest mistreatment and discrimination, especially as experienced by farm workers, many others focus on love of family and for the land and traditions of his people. Delgado wrote and self-published 14 books of poetry⁰́₄none of which are available today⁰́₄and five of them are included in this long-awaited volume. These poems by a pioneering Chicano poet and revolutionary are a must-read for anyone interested in the Chicano Civil Rights movement and the origins of Chicano literature.